Gerakan Fajar Nusantara: Sebuah Proyek Agonistik (?) - William Christopher Hariandja (Retorik: Jurnal Ilmu Humaniora, 2022)
The Fajar Nusantara Movement, also known as GAFATAR was born as a “religion” and a new movement. Through this paper, I discuss the existence of GAFATAR. The discussion begin by looking at the context in which GAFATAR was born, especially after the movement was widely known due to mass media coverage. After that, I will see GAFATAR as an antagonism vis a vis state in its position. To discuss these problems, I use the method of writing observation literature. The object of study to be examined is: “To what extent can the GAFATAR movement be seen as an antagonism?” Then, the object material from the observation of the literature refers to two things: (1) the history of the birth of GAFATAR and (2) the dynamics of the GAFATAR movement. Limiting the scope of discussion, I choose to see GAFATAR as a political movement, thus setting aside the dogmatic teaching of Islam, which is also the background to the birth of GAFATAR. The purpose of this limitation is to allow the position of GAFATAR to be seen as a new social movement. This paper will focus on understanding GAFATAR as an agonistic project by considering it from the theoretical perspectives of Ernesto Laclau and Chantal Mouffe.